1998
DOI: 10.1101/gad.12.17.2711
|View full text |Cite
|
Sign up to set email alerts
|

okra and spindle-B encode components of the RAD52 DNA repair pathway and affect meiosis and patterning in Drosophila oogenesis

Abstract: okra (okr), spindle-B (spnB), and spindle-D (spnD) are three members of a group of female sterile loci that produce defects in oocyte and egg morphology, including variable dorsal-ventral defects in the eggshell and embryo, anterior-posterior defects in the follicle cell epithelium and in the oocyte, and abnormalities in oocyte nuclear morphology. Many of these phenotypes reflect defects in grk-Egfr signaling processes, and can be accounted for by a failure to accumulate wild-type levels of Gurken and Fs(1)K10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
235
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(251 citation statements)
references
References 45 publications
15
235
0
Order By: Relevance
“…The following mutations were used and have been previously described: spn-A 1 , spn-A 093 , spn-B BU , and spn-D 150 (Ghabrial et al 1998;Abdu et al 2003;Jang et al 2003;Staeva-Vieira et al 2003), mei-218 1 , mei-218 6 (Carpenter and Sandler 1974;McKim et al 1996), rec 1 and rec 2 (Blanton et al 2005), and lig4 57 (Gorski et al 2003;Romeijn et al 2005). Experiments with rec were done with rec 1 /rec 2 heterozygotes.…”
Section: Fly Stocks and Genetic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The following mutations were used and have been previously described: spn-A 1 , spn-A 093 , spn-B BU , and spn-D 150 (Ghabrial et al 1998;Abdu et al 2003;Jang et al 2003;Staeva-Vieira et al 2003), mei-218 1 , mei-218 6 (Carpenter and Sandler 1974;McKim et al 1996), rec 1 and rec 2 (Blanton et al 2005), and lig4 57 (Gorski et al 2003;Romeijn et al 2005). Experiments with rec were done with rec 1 /rec 2 heterozygotes.…”
Section: Fly Stocks and Genetic Techniquesmentioning
confidence: 99%
“…Thus, mutation of Drosophila Rad51, spn-A, and its paralogs spn-D and spn-B, block meiotic DSB repair and accumulate DSBs into late stages of pachytene, as detected by an antibody to the phosphorylated form of H2AV (Ghabrial et al 1998;Ghabrial and Schupbach 1999;Abdu et al 2003;Jang et al 2003;Staeva-Vieira et al 2003;Mehrotra and McKim 2006). spn-D and spn-B encode orthologs of RAD51C and XRCC3, respectively, which are believed to function as a heterodimer in mammalian cells to promote DSB repair by homologous recombination (HR) (Kurumizaka et al 2001;Abdu et al 2003;Sung et al 2003;Radford and Sekelsky 2004).…”
mentioning
confidence: 99%
“…5). Interestingly, several genes have been shown to be involved in the control of grk mRNA or protein localization and grk translation [aubergine (aub); cornichon (cni); encore; K10;maelstom;okra;orb;spinB;spinD;vasa;Roth et al 1995;Neuman-Silberberg and Schü pbach 1996;Wilson et al 1996;Clegg et al 1997;Hawkins et al 1997;Ghabrial et al 1998;Styhler et al 1998;Tomancak et al 1998), thus defining a pathway that is important for post-transcriptional regulation of grk and subsequent EGFR signaling. In these mutants, aspects of grk function are altered, leading to AP and DV defects reminiscent of those observed in lic.…”
Section: P38 and Erk Mapk Pathways Interact During Oogenesismentioning
confidence: 99%
“…Despite this general view and the fact that several gene products have been identified that participate in these dynamic events, the biochemical interactions that take place are still poorly understood. In addition, genetic screens have revealed that several molecularly uncharacterized genes may have a role in these processes, leading to the notion that the development of the egg chamber is more complex and requires additional gene activities and regulatory mechanisms yet to be identified (Ghabrial et al 1998).…”
mentioning
confidence: 99%
“…RAD51B, RAD51D, and XRCC2 knockout mutant mice died during embryonic development (Shu et al, 1999;Deans et al, 2000;Pittman and Schimenti, 2000). The RAD51C and XRCC3 mutants in Drosophila (Spn-D and Spn-B, respectively) were partially sterile, defective for meiotic recombination, but not hypersensitive to DSB-inducing agents (Ghabrial et al, 1998;Abdu et al, 2003).…”
mentioning
confidence: 99%